Structural Analysis of Bukit Bunuh Impact Crater using Transient Electromagnetic Method - Khairul Arifin Mohd Noh, Muhammad Hasif Syazwan Shamsul, Mohd Mo, . (2015)
Bukit Bunuh is believed to be a site of a complex impact crater which occurred during the Quaternary age. According to Ferriere (2012), the presence of an impact crater is proven by diagnostic shock metamorphism features both on macroscopic and microscopic level such as shatter cones, planar deformation features, etc.